2013
DOI: 10.1186/1472-6963-13-395
|View full text |Cite
|
Sign up to set email alerts
|

Impact of telehealth on general practice contacts: findings from the whole systems demonstrator cluster randomised trial

Abstract: BackgroundTelehealth is increasingly used in the care of people with long term conditions. Whilst many studies look at the impacts of the technology on hospital use, few look at how it changes contacts with primary care professionals. The aim of this paper was to assess the impacts of home-based telehealth interventions on general practice contacts.MethodSecondary analysis of data from a Department of Health funded cluster-randomised trial with 179 general practices in three areas of England randomly assigned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…However, many studies fail to report positive outcomes (Olazaran et al, 2010). For example, recent pragmatic trials of support programmes (Kurz et al, 2012;Low et al, 2013;Van de Ven et al, 2013;Waldorff et al, 2012), telecare (Bardsley, Steventon, & Doll, 2013), training interventions (Beer et al, 2011;Spijker et al, 2011) and system enhancements or novel methods of delivering services (Goldberg et al, 2013;Meeuwsen et al, 2012;Nourhashemi et al, 2010;Van Houdt & De Lepeleire, 2010) all report no positive effects compared with the control 'usual care' condition. One study nonetheless demonstrated improvements in the patient experience and family carer satisfaction (Goldberg et al, 2013) whilst others point to problems with delivery of the intervention by practitioners such as poor adherence and variation in practice (Low et al, 2013;Spijker et al, 2013;Wenborn et al, 2013).…”
Section: Success and Failure Of Psychosocial Interventionsmentioning
confidence: 99%
“…However, many studies fail to report positive outcomes (Olazaran et al, 2010). For example, recent pragmatic trials of support programmes (Kurz et al, 2012;Low et al, 2013;Van de Ven et al, 2013;Waldorff et al, 2012), telecare (Bardsley, Steventon, & Doll, 2013), training interventions (Beer et al, 2011;Spijker et al, 2011) and system enhancements or novel methods of delivering services (Goldberg et al, 2013;Meeuwsen et al, 2012;Nourhashemi et al, 2010;Van Houdt & De Lepeleire, 2010) all report no positive effects compared with the control 'usual care' condition. One study nonetheless demonstrated improvements in the patient experience and family carer satisfaction (Goldberg et al, 2013) whilst others point to problems with delivery of the intervention by practitioners such as poor adherence and variation in practice (Low et al, 2013;Spijker et al, 2013;Wenborn et al, 2013).…”
Section: Success and Failure Of Psychosocial Interventionsmentioning
confidence: 99%
“…9 Pinnock and colleagues report that the introduction of telehealth has resulted in increasing contact between patients and GPs, 10 although this was contradicted in another study on GP and practice nurse contacts with patients which showed no change. 11 The qualitative study reported here is a component of the Whole System Demonstrator evaluation, a large cluster randomised controlled trial of telehealth and telecare for patients with long-term and complex conditions (chronic heart disease, chronic obstructive pulmonary disease [COPD] and diabetes) and those with social care needs. Details of the trial design are reported elsewhere 12 but are summarised here in Box 1 and Box 2.…”
Section: Introductionmentioning
confidence: 99%
“…However, a German PHC-based study showed that a patient with HF had six visits to their GP. Meanwhile, in an English study, there were nine visits to the GP (95,117). These divergent findings possibly illustrate that PHC differs in European countries and that these studies had somewhat different populations.…”
Section: Healthcare Utilization Of Heart Failurementioning
confidence: 98%